A Novel Mutation in ATRX Causes Alpha-Thalassemia X-Linked Intellectual Disability Syndrome in a Han Chinese Family - Wu, Shaomin; Zheng, Yingchun; Xu, Cailing; Fu, Jiahui; Xiong, Fu; Yang, Fang (Frontiers in Pediatrics, 2022)
Objective: To analyze genetic mutations in a Chinese pedigree affected with Alpha-thalassemia X-linked intellectual disability syndrome, providing a precise diagnosis and genetic counseling. Methods: Clinical data was collected. A novel alternative splicing variant detected by whole-exome sequencing was validated by Sanger sequencing. The functional effect of the mutation was predicted with Mutation Tasting. The analysis of 5' splice site score was estimated with MaxEntScan. Changes in amino acid sequencing were predicted with Mutalyzer. The tertiary structures of the wild type and mutation-carrying protein were predicted by I-TASSER. RNA was extracted from peripheral blood lymphocytes from the proband, his mother and a healthy control. Quantitative Real-Time PCR was used to detect mRNA expression. Results: The proband presented with severe intellectual disability, developmental delay, characteristic facies, seizures and cryptorchidism. A novel hemizygous duplication mutation in the ATRX gene in a splice site between exons 3 and 4, NM_000489: c.189+1dupG, was identified with WES in the proband. Sanger sequencing confirmed that the mutation was inherited from his mother, who carried a heterozygous mutation, while his father was not affected. Bioinformatics analysis indicated that the splicing region where the mutation was located is highly conserved and the variant was damaging, producing a truncated protein due to the premature translation of a stop codon. Sanger sequencing with the Quantitative Real-Time PCR product containing a G base inserted between bases 189 and 190. The level of mRNA expression showed that ATRX gene transcription decreased due to the mutation (P < 0.05). Conclusions: A novel mutation in ATRX was found in this pedigree and was confirmed to be pathogenic through functional studies. Our research expanded the spectrum of ATRX gene mutations, providing a precise diagnosis and a basis for genetic counseling.